Genetic Analysis of a Cryptosporidium parvum Human Genotype 1 Isolate Passaged through Different Host Species - Akiyoshi, D. E. (American Society for Microbiology, 2002)
Cryptosporidium parvum TU502, a genotype 1 isolate of human origin, was passaged through three different mammalian hosts, including humans, pigs, and calves. It was confirmed to be genotype 1 by PCR-restriction fragment length polymorphism analysis of the Cryptosporidium oocyst wall protein gene, direct sequencing of PCR fragments of the small subunit rRNA and β-tubulin genes, and microsatellite analysis. This isolate was shown to be genetically stable when passaged through the three mammalian species, with no evidence of the emergence of new subpopulations as observed by a genotype-specific PCR assay. TU502 oocysts from different sources failed to infect gamma interferon knockout mice, a characteristic of genotype 1 isolates. The genotypic and phenotypic characterization of TU502 is significant since it is the isolate selected to sequence the genome of C. parvum genotype 1 and is currently used in several research projects including human volunteer studies.